2019
DOI: 10.3390/cancers11111755
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Nrf2 Activity in Cancer Development and Progression

Abstract: Nrf2 is a transcription factor that stimulates the expression of genes which have antioxidant response element-like sequences in their promoter. Nrf2 is a cellular protector, and this principle applies to both normal cells and malignant cells. While healthy cells are protected from DNA damage induced by reactive oxygen species, malignant cells are defended against chemo- or radiotherapy. Through our literature search, we found that Nrf2 activates several oncogenes unrelated to the antioxidant activity, such as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
150
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 206 publications
(153 citation statements)
references
References 168 publications
(140 reference statements)
2
150
0
1
Order By: Relevance
“…Interestingly, studies have shown that systemic upregulation of NRF2 can be radioprotective [ 60 ], while our own previous work has indicated that bixin can upregulate NRF2 systemically causing skin photoprotection [ 28 , 61 ]. However, in the context of this study, topical bixin administration seems preferable as it could limit NRF2 induction to the skin, thus minimizing NRF2 modulation throughout the body, and ultimately maintaining the desired sensitivity of specific tissues to radiotherapy [ [62] , [63] , [64] ]. While IR effects on cultured and epidermal keratinocytes are the primary focus of these experiments, the role of inflammatory factors including immune cell infiltration and response, all of which might be subject to modulation by NRF2, deserves further studies as it was not addressed in this prototype investigation.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, studies have shown that systemic upregulation of NRF2 can be radioprotective [ 60 ], while our own previous work has indicated that bixin can upregulate NRF2 systemically causing skin photoprotection [ 28 , 61 ]. However, in the context of this study, topical bixin administration seems preferable as it could limit NRF2 induction to the skin, thus minimizing NRF2 modulation throughout the body, and ultimately maintaining the desired sensitivity of specific tissues to radiotherapy [ [62] , [63] , [64] ]. While IR effects on cultured and epidermal keratinocytes are the primary focus of these experiments, the role of inflammatory factors including immune cell infiltration and response, all of which might be subject to modulation by NRF2, deserves further studies as it was not addressed in this prototype investigation.…”
Section: Discussionmentioning
confidence: 99%
“…Such surprising result implies that Nrf2 may also contribute to ROS production in Nrf1α / cells under basal and glucose deprivation conditions, albeit it has been accepted as a master regulator of antioxidant cytoprotective genes [44]. This is also supported by the finding that Nrf1α / cells are maintained at higher ROS levels in almost unstressed conditions, while Nrf2 −/− cells are preserved at relatively lower ROS levels than those of wild-type Nrf1/2 +/+ cells (in this study).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, basal Nrf2 levels can increase during chemo-or radiotherapy, which correlates with therapy resistance [173]. On the other hand, Nrf2 plays a protective role and prevents cancer development by reducing ROS levels [172,173]. This implies a dual role for Nrf2 in cancer development and suggests that optimal therapy likely depend on cancer stage or cancer type, as summarized in Milkovic et al [176].…”
Section: The Nrf2-keap1 Signaling Pathwaymentioning
confidence: 99%
“…The exact role of Nrf2 in carcinogenesis remains unclear. On the one hand, it has been shown that Nrf2 is upregulated in various cancers [172,173], which is caused either by DNA methylation in the promoter region of Keap1, constitutive Nrf2 activation, or mutations in the Keap1 domain [174,175]. Furthermore, basal Nrf2 levels can increase during chemo-or radiotherapy, which correlates with therapy resistance [173].…”
Section: The Nrf2-keap1 Signaling Pathwaymentioning
confidence: 99%